Landschaftsökologische Grundlagenforschung in Trockengebieten. Dargestellt an Beispielen aus der Kalahari und ihren Randlandschaften - Leser, Hartmut (ERDKUNDE, 1971)
Landscape changes in South and South West Africa which have occurred as a result of overuse of arable or grazing land are as worthy of research in physical geography as the landscapes which have been little or entirely untouched by man. The investigation of landscape content forms part of an analysis of landscape ecology. Its values must be considered at all levels of landscape discussion so that a quantitative estimate will emerge from the general classification of natural physical units. A determination of natural potential for economic development can emerge from the content analysis of natural physical units. In this way a proper, environmentally adjusted use can be achieved. Using the example of the peripheral landscapes of the Kalahari, it is shown that use has already made serious inroads into the landscape budget which will be difficult to correct. Because of this, a physiogeographical inventory should always precede planning and use; this inventory should not only encompass all the geofactors but also take into account the varying dimen ions of the natural areas.